Utilization of optical heart rate and electrocardiogram sensors as signal indicators during exercise in woodball - Indra Kusuma, Angga; Utamayasa, I Gede Dharma; Harwanto (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to examine the effectiveness of optical heart rate (OHR) and electrocardiogram (ECG) sensors as signal indicators in sports, particularly in the woodball game. The relevant and chosen approach was quantitative research with a quasi-experimental method using a matching-only design. The study involved a total of 64 participants (mean age 15.2±1.5 years; mean height 165.4±6.2 cm; mean weight 58.3±7.8 kg; BMI 21.3±2.1 kg/m²), divided equally into two groups: 32 athletes in the experimental group and 32 athletes in the control group. Treatment for the experimental group involved gate-in-one stroke training and 24-gate competition training using OHR and ECG sensors in the form of fitness trackers. Meanwhile, the control group followed only the conventional training routines conducted by each club. Data collection techniques using pre-test and post-test in this study employed a gate-in-one stroke test instrument. The results of this study indicated that OHR and ECG sensors, packaged in the form of a fitness tracker, can significantly support athletes in conducting sports activities (p=0.032), showing a meaningful improvement in performance and accuracy in woodball. Relating to this, the technology can have a significant effect on improving skills, especially accuracy in the woodball game. In conclusion, OHR and ECG sensors can serve as signal indicators during exercise in sports.